Emerging trends of use of Complementary Alternative Medicine in Asthmatics - Rehman, Rehana; Naz, Ayesha Saba; Khan, Rakhshaan; Hashmi, Faisal; Ejaz, Yasir (Journal of Postgraduate Medical Institute, 2013)
Objective: Objective: To compare awareness and usage of various complementary alternative medicine (CAM) modalitiesin patients with asthma. Methodology: An observational cross sectional study conducted at Pulmonology clinics on 452 male andfemale patients. Their age ranged from 10 till 50 years. An interview based questionnaire tested knowledgeand use of CAM by intake of; tea, coffee, soups, joshanda, misri and honey, involvement by; yoga, swimmingand breathing exercises along with application of CAM modalities like Vicks and steam inhalation. Results: It was found that males had greater awareness and used modalities of CAM more than females.The age stratum reflecting maximum awareness was shown by the age group of 31-40 years with the femalessignificantly having more knowledge(p= 0.01). The knowledge was significant in patients who hadfamily predisposition of seasonal allergies and had frequently been using inhalers. Application of CAMwas seen with modalities of homeopathic and herbal medicines, coffee intake, steam inhalation, breathingexercises and use of multivitamins (p value<0.05). The knowledge of use of swimming was found in 56%of asthmatics. A high ratio of respondents had knowledge of role of honey, soups, yoga exercises andapplication of Vicks vaporub but practices of these modalities were not found to be significant. Practiceof swimming, intake of tea, soup/broth, honey; and application of Vicks was not found to be popular amongpatients with asthma. Conclusion: Patients with asthma were acquainted and used some adjuvants together with prescribedmedicines as component of CAM; however its awareness was greater as compared to its usage.